Cardiovascular Disease Risk–Based Statin Utilization and Associated Outcomes in a Primary Prevention Cohort: Insights From a Large Health Care Network. Issue 9 (September 2021) - Saeed, Anum; Zhu, Jianhui; Thoma, Floyd; Marroquin, Oscar; Aiyer, Aryan; Agarwala, Anandita; Virani, Salim S.; Gulati, Martha; Lee, Joon S.; Reis, Steven; Saba, Samir; Ballantyne, Christie; et al.
Abstract : Background: Current American College of Cardiology/American Heart Association guidelines recommend using the 10-year atherosclerotic cardiovascular disease (ASCVD) risk to guide statin therapy for primary prevention. Real-world data on adherence and consequences of nonadherence to the guidelines in primary are limited. We investigated the guideline-directed statin intensity (GDSI) and associated outcomes in a large health care system, stratified by ASCVD risk. Methods: Statin prescription in patients without coronary artery disease, peripheral vascular disease, or ischemic stroke were evaluated within a large health care network (2013–2017) using electronic medical health records. Patient categories constructed by the 10-year ASCVD risk were borderline (5%–7.4%), intermediate (7.5%–19.9%), or high (≥20%). The GDSI (before time of first event) was defined as none or any intensity for borderline, and at least moderate for intermediate and high-risk groups. Mean (±SD) time to start/change to GDSI from first interaction in health care and incident rates (per 1000 person-years) for each outcome were calculated. Cox regression models were used to calculate hazard ratios for incident ASCVD and mortality across risk categories stratified by statin utilization. Results: Among 282 298 patients (mean age ≈50 years), 29 134 (10.3%), 63 299 (22.4%), and 26 687 (9.5%) were categorized as borderline, intermediate, and high risk, respectively. Among intermediate and high-risk categories, 27 358 (43%) and 8300 (31%) patients did not receive any statin, respectively. Only 17 519 (65.6%) high-risk patients who were prescribed a statin received GDSI. The mean time to GDSI was ≈2 years among the intermediate and high-risk groups. At a median follow-up of 6 years, there was a graded increase in risk of ASCVD events in intermediate risk (hazard ratio=1.15 [1.07–1.24]) and high risk (hazard ratio=1.27 [1.17–1.37]) when comparing no statin use with GDSI therapy. Similarly, mortality risk among intermediate and high-risk groups was higher in no statin use versus GDSI. Conclusions: In a real-world primary prevention cohort, over one-third of statin-eligible patients were not prescribed statin therapy. Among those receiving a statin, mean time to GDSI was ≈2 years. The consequences of nonadherence to guidelines are illustrated by greater incident ASCVD and mortality events. Further research can develop and optimize health care system strategies for primary prevention. Abstract : Supplemental Digital Content is available in the text.